Assessment of genetic diversity in Cattleya intermedia Lindl. (Orchidaceae) - Nelson Barbosa Machado Neto; Luiz Gonzaga Esteves Vieira (Brazilian Archives of Biology and Technology, 2011)
Orchids are valuable pot plants and Cattleya intermedia is a promising species underused in breeding programs. Recently, breeding work with this species produced superior plants that are believed to be not the true species owing to the morphological differences from wild plants. The aim of this study was to estimate the level of genetic diversity and interrelationships between wild and bred Cattleya intermedia collected at three different Brazilian states and from commercial breeders with RAPD markers. A total of 65 polymorphic bands were used to generate a genetic distance matrix. No specific groupings were revealed by the cluster analysis as bred materials were not different from wild plants. The genetic differentiation (F ST = 0.01626) was very low indicating a high gene flow in C. intermedia due to artificial crosses and a high differentiation between populations. The genetic variability available within this species is high enough to allow genetic progress in flower shape and size.